Management of Guidance and Counselling Services in Directing Students for Career Selection - Usman, Intan Nurfitri; Widayatsih, Tri; Eddy, Syaiful (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to describe (1) Planning, implementation, and supervision; (2) Obstacles faced and solutions in managing guidance and counseling services to direct students in choosing a career at SMA Negeri 14 Ogan Komering Ulu. This research is qualitative research with a case study method. Data collection used in this research included (1) in-depth interviews (Depth interview), (2) participant observation (participant observation), and (3) documentation. Based on this research, the results obtained are that 1) Planning, implementation, and management supervision of guidance services to direct students in career choices has gone quite well; 2) The obstacles faced by SMA Negeri 14 OKU in managing guidance and counseling services are internal factors, lack of depth in career determination, inadequate facilities and infrastructure, and teachers' busy teaching schedules; In overcoming these obstacles, four solutions have been implemented, namely 1) collaboration between BBK teachers and school personnel, 2) making a list of guidance service activities, 3) completing facilities and infrastructure BK room, and 4) manage a good time.